Rhizosphere soil microbial community and its response to different utilization patterns in the semi-arid alpine grassland of northern Tibet - Fu, Lijiao; Yan, Yan; Li, Xueqin; Liu, Yanling; Lu, Xuyang (Frontiers in Microbiology, 2022)
As the link between plants and soils, rhizosphere soil microorganisms play an important role in the element cycle. This study aimed to understand the response of rhizosphere soil microbial community structure and interaction network to grassland utilization in the alpine steppe of the northern Tibet Plateau. High-throughput sequencing was employed to study the composition, diversity, and species interaction network of rhizosphere soil microbial communities under grazing, mowing, and enclosing treatments. Proteobacteria (47.19%) and Actinobacteria (42.20%) were the dominant bacteria in the rhizosphere soil. There was no significant difference in relative abundance among rhizosphere soil microorganisms at phylum and genus levels, but differences were found in Chlorobi, Ignavibacteriae, and Micromonospora. Alpha diversity index based on Shannon, Chao1, and Simpson indices revealed that, except for a significant difference in the Shannon index of the Artemisia nanschanica group, the richness and evenness of rhizosphere soil microbial communities among all groups were similar. Nonmetric multidimensional scaling (NMDS) and multi-response permutation procedure (MRPP) analyses showed that the inter-group differences of three plants (Stipa purpurea, Carex moorcroftii and Artemisia nanschanica) were greater than that the differences within the groups; however, only the inter-group difference with the Stipa purpurea group was significant. The microbial interaction network showed that the network complexity of the Artemisia nanschanica group and the enclosing treatment, which were not easily disturbed by external factors, was higher than that of the other groups and treatments; this again demonstrated that Proteobacteria and Actinobacteria were the network core microbial species in alpine steppe of the northern Tibet Plateau and were crucial for maintaining stability of the microbial communities. Findings from this study provide a theoretical basis for the restoration of degraded alpine grassland and the development of microbial functions.